South American Stoneflies (Plecoptera) (2009)
Urban streams have been the focus of much research in recent years, but many questions about the mechanisms driving the urban stream syndrome remain unanswered. Identification of key research questions is an important step toward effective, efficient management of urban streams to meet societal goals. We developed a list of priority research questions by: 1) soliciting input from interested scientists via a listserv and online survey, 2) holding an open discussion on the questions at the Second Symposium on Urbanization and Stream Ecology, and 3) reviewing the literature in the preparation of this paper. We present the resulting list of 26 questions in the context of a review and summary of the present understanding of urban effects on streams. The key questions address major gaps in our understanding of ecosystem structure and function responses (e.g., what are the sublethal impacts of urbanization on biota?), characteristics of urban stream stressors (e.g., can we identify clusters of covarying stressors?), and management strategies (e.g., what are appropriate indicators of ecosystem structure and function to use as management targets?). The identified research needs highlight our limited understanding of mechanisms driving the urban stream syndrome and the variability in characteristics of the effects of urbanization across different biogeoclimatic conditions, stages of development, government policies, and cultural norms. We discuss how to proceed with appropriate management activities given our current incomplete understanding of the urban stream syndrome.